The Influence of Temperature and Drying Time on The Physical and Chemical Characteristics of Cocoa Pod Tea Theobroma (Cacao, L.) - Lembong, Elazmanawati; Nurhasanah, Siti; Subroto, Edy; Maharani, Dewanti; Fadhillah, Ayesha Nur (Journal of Applied Science, Engineering, Technology, and Education, 2024)
Cocoa is one of the plantation products that plays an important role in the Indonesian economic sector because it contains many nutrients that provide health effects on the body, one of which is high antioxidant content. Processing of cocoa shell waste in the food industry can be optimized. One process of utilizing cocoa shell waste is processing it into tea. The drying process affects the resulting cocoa husk tea. In addition, drying temperature also affects the antioxidant content of a food product. The drying process for this research used a food dehydrator. It produces a large driving force of drying air so that it can remove the water content in the ingredients. This research aims to determine the temperature and drying time using a food dehydrator, which produces cocoa husk tea and has characteristics according to Indonesian National Standard (SNI). The research methods used experimental and descriptive analysis. The treatment used in this research employed a food dehydrator temperature, by 50°C, 55°C, 60°C, and 65°C with a drying time of 4.5 hours and 6 hours respectively. The results of this research indicated that the temperature and drying time were 50°C and 4.5 hours to produce cocoa husk tea according to SNI with 8,018% water content and 7,98% ash content.